Hazards of electricity - Knowlton, Robert A. (Texas : Gulf Publishing Company, 1993)
Focuses on safetu of using electrical equipment and also explain on injury that cause by electrical equipment especially hazards of electricity
Keywords: Electric engineering -- Safety measures